Effect of Salmonella Typhimurium on guinea pig carcass (Cavia porcellus) - Bazán R., Víctor (2022)
The objective was to determine the effect of Salmonella Typhimurium on the chemical composition and microbiological quality of the meat of guinea pig (Cavia porcellus). 30 male guinea pigs for fattening were used that were distributed in 3 treatments with ten (10) repetitions each; T1: mixed feeding + saline solution (control), T2: mixed feeding and experimentally challenged with Salmonella Typhimurium, T3: mixed feeding + APC (antibiotic growth promoter) and experimentally challenged with Salmonella Typhimurium. T1 animals were dosed orally with saline solution, while T2 and T3 were challenged with an infective dose (2 x 106 CFU) of Salmonella Typhimurium, only once on the 11th day of the start of the experiment. Despite manifesting the disease in animals challenged with Salmonella, they did not show differences (p <0.05) in the concentration of protein and ethereal extract on a dry basis. The microbiological results showed the presence of Salmonella in the lymph nodes, liver, lung, spleen and gallbladder in the experimentally infected animals. The use of APC in T3 did not improve the chemical composition of guinea pig meat.